Ternary positive electrode material and preparation method and application thereof
The ternary positive electrode material is prepared through an improved sintering process, which solves the problem of lithium-ion batteries charging and degradation of lithium-ion battery life in low-temperature environments, and achieves high power and high stability low-temperature charging and discharging performance, avoiding the scarcity of Co resources. question.
Patent Information
- Application Number
- CN202411307953.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
Lithium-ion batteries charge lithium-ion batteries in low-temperature environments, have large polarization and reduced battery life. The existing technology relies on increasing the content of Co elements to improve low-temperature performance, but Co resources are scarce, so technology with high universality and low cost is needed.
Adopt an improved sintering process, mix part of the doped elements during the first sintering, mix the coating agent during the second sintering, and mix another part of the doped elements during the third sintering, and strictly control the parameters of each sintering to improve doping and coating. Uniformity, control particle size, and prepare ternary positive electrode materials with high dynamics and high stability.
Maintaining high charge and discharge performance in a low-temperature environment improves the power and stability of the ternary positive electrode material, and solving the problem of low-temperature performance of lithium-ion batteries.
Smart Images

Figure CN119284979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are currently widely used in 3C consumer products and power batteries, and have good development prospects. However, in winter, especially in northern my country, when the temperature drops below -20°C, the performance of lithium-ion batteries is greatly reduced due to the increase in electrolyte viscosity and the poor diffusion rate of lithium ions in electrode materials. Charging at low temperatures will cause lithium precipitation, which seriously affects the safety performance of lithium-ion batteries; at the same time, polarization is too large at low temperatures, and it is easy to reach the cut-off voltage during discharge, so the battery life is reduced. How to improve the low-temperature performance of lithium-ion batteries has become one of the important directions of current lithium-ion battery research.
[0003] The current mainstream positive electrode materials are ternary (LiNi x Co y Mn (1-x-y) In order to improve the low-temperature charge and discharge performance of ternary materials, it is generally achieved by improving the conductivity of the material, such as increasing the content of Co. Although increasing the content of Co has a good effect on improving low temperature, due to the relative scarcity of Co resources, it is urgent to develop a new type of ternary low-temperature improvement technology with high universality and low cost.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a ternary positive electrode material and a preparation method and application thereof. The ternary positive electrode material prepared by the preparation method of the ternary positive electrode material has high power and high stability, and exhibits excellent low-temperature charge and discharge performance at low temperatures.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] One aspect of the present invention relates to a method for preparing a ternary positive electrode material, comprising the following steps:
[0008] (a) sintering and pulverizing a mixed system containing a lithium source, a ternary precursor and a first doping element;
[0009] (b) subjecting the mixed system containing the pulverized product and the coating agent to secondary sintering;
[0010] (c) sintering a mixed system containing the secondary sintered product and the second doping element for a third time to obtain the ternary positive electrode material.
[0011] The method for preparing the ternary positive electrode material is simple and does not rely on strict equipment or conditions. The prepared ternary positive electrode material has high power and high stability and can exhibit excellent low-temperature charge and discharge performance in a low-temperature environment.
[0012] Another aspect of the present invention also relates to a ternary positive electrode material prepared by the method for preparing the ternary positive electrode material.
[0013] The ternary positive electrode material has high power and high stability, and can exhibit excellent low-temperature charge and discharge performance in a low-temperature environment.
[0014] Another aspect of the present invention also relates to a positive electrode plate, including the ternary positive electrode material prepared by the preparation method of the ternary positive electrode material or the ternary positive electrode material.
[0015] Another aspect of the present invention also relates to a secondary battery, comprising the positive electrode plate.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The preparation method of the ternary positive electrode material provided by the present invention adopts an improved sintering process, wherein a portion of the doping elements are mixed in during the first sintering, a coating agent is mixed in during the second sintering, and another portion of the doping elements is mixed in during the third sintering, and the parameters of each sintering are strictly controlled. Through step-by-step sintering, the uniformity of doping and coating is improved, and the particle size is effectively controlled, thereby improving the power and stability of the ternary positive electrode material, so that the ternary positive electrode material still has good charge and discharge performance in a low temperature environment.
[0018] (2) The ternary positive electrode material provided by the present invention has high power and stability, and can still maintain high charge and discharge performance in a low temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is an XPS spectrum of oxygen element provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0022] One aspect of the present invention relates to a method for preparing a ternary positive electrode material, comprising the following steps:
[0023] (a) sintering and pulverizing a mixed system containing a lithium source, a ternary precursor and a first doping element;
[0024] (b) subjecting the mixed system containing the pulverized product and the coating agent to secondary sintering;
[0025] (c) sintering a mixed system containing the secondary sintered product and the second doping element for a third time to obtain the ternary positive electrode material.
[0026] The preparation method of the ternary positive electrode material adopts an improved sintering process, a part of the doping elements are mixed in the first sintering, a coating agent is mixed in the second sintering, and another part of the doping elements are mixed in the third sintering, and the parameters of each sintering are strictly controlled, thereby improving the power and stability of the ternary positive electrode material, so that the ternary positive electrode material still has good charge and discharge performance in a low temperature environment.
[0027] Furthermore, the primary sintering temperature is 820-940°C, including but not limited to any point value of 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C or 940°C, or a range value between any two of them.
[0028] Furthermore, the primary sintering time is 10 to 20 hours, including but not limited to any one of 10 hours, 12 hours, 14 hours, 16 hours, 18 hours or 20 hours or a range between any two of them.
[0029] Further, the temperature of the secondary sintering is 700-900°C, including but not limited to any point value of 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C or 900°C or the range value between any two of them.
[0030] Furthermore, the secondary sintering time is 6 to 12 hours, including but not limited to any one of 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, or a range between any two of them.
[0031] Furthermore, the temperature of the three sinterings is 400-500°C, including but not limited to any point value of 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C or 500°C or the range value between any two of them.
[0032] Furthermore, the time for the three sinterings is 1 to 3 hours, including but not limited to any one of 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours or a range between any two of them.
[0033] Furthermore, the coating agent includes at least one of CoO, CoOOH, Co2O3, Co3O4, NiO or Ni2O3. There is no specific limitation on the amount of the coating agent added, as long as it meets the molecular formula of the final ternary positive electrode material.
[0034] Furthermore, the ratio of the molar number of lithium in the lithium source to the total molar number of the first doping element and the second doping element is 0.98-1.05:0.01-0.01.
[0035] The present invention does not specifically limit the specific types and amounts of the first doping element and the second doping element during the two sintering processes, as long as the amounts of the doping elements ultimately conform to the molecular formula of the ternary positive electrode material.
[0036] Furthermore, the first doping element includes but is not limited to: at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb or Ta.
[0037] Furthermore, the second doping element includes but is not limited to at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb or Ta.
[0038] Furthermore, the chemical formula of the ternary precursor is Ni a Co b Mn (1-a-b) (OH)2, wherein 0.55≤a≤0.75, 0.02≤b≤0.15.
[0039] Furthermore, the molar ratio of lithium in the lithium source to nickel in the ternary precursor is 0.98-1.05:0.55-0.75.
[0040] Furthermore, the primary sintered product is dispersed into single crystal particles by air flow pulverization.
[0041] The present invention does not limit the specific type of lithium source, and conventional lithium sources in the art can be used to implement the technical solution of the present invention. In some specific embodiments, the lithium source includes but is not limited to: lithium carbonate and / or lithium hydroxide.
[0042] Another aspect of the present invention also relates to a ternary positive electrode material prepared by the method for preparing the ternary positive electrode material.
[0043] The ternary positive electrode material has high power and stability, and can still maintain high charge and discharge performance in a low temperature environment.
[0044] Furthermore, the molecular formula of the ternary cathode material is Li x Ni y Co z Mn (1-y-z) M q O (2-t) ;
[0045] Among them, 0.98≤x≤1.05, 0.55≤y≤0.75, 0.02≤z≤0.15, 0≤q≤0.01, 0≤t≤0.01, and M includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb or Ta.
[0046] Another aspect of the present invention also relates to a positive electrode plate, including the ternary positive electrode material prepared by the preparation method of the ternary positive electrode material or the ternary positive electrode material.
[0047] Another aspect of the present invention also relates to a secondary battery, comprising the positive electrode plate.
[0048] Definition of oxygen deficiency rate: Figure 1 As shown in the XPS test results, the peak heights corresponding to the two binding energies are Pa and Pb, the oxygen defect rate Od = Pb / (Pa+Pb), and the optimal range of the oxygen defect rate Od is 54-66%. The larger the Od, the more surface defects there are, which is more conducive to the diffusion of lithium ions on the surface, but at the same time it will deteriorate the high temperature stability, so there is an optimal range.
[0049] The optimal range of volume distribution Dmin / D50 is 0.05-0.12, which controls the size of small particles. The smaller the small particles, the better the low-temperature dynamics. However, if the small particles are too small, the high-temperature performance will deteriorate. Therefore, there is an optimal range.
[0050] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0051] Example 1
[0052] The method for preparing the ternary positive electrode material provided in this embodiment comprises the following steps:
[0053] 1. During the primary mixing process, lithium source, precursor and first doping element M1 are added in proportion and then sintered. After sintering to the sintering temperature, the temperature is kept constant. Then, the particles are dispersed into single crystal particles by air flow pulverization.
[0054] 2. Add coating agent during the secondary mixing process and perform secondary sintering;
[0055] 3. Add the second doping element M2 during the three mixing processes, perform secondary sintering, and keep the temperature after sintering to the sintering temperature.
[0056] The specific general formula and sintering conditions of the ternary positive electrode material are shown in Table 1.
[0057] Embodiment 2 to Embodiment 9
[0058] The preparation steps of Examples 2 to 9 are the same as those of Example 1. The specific general formula of the ternary positive electrode material and the sintering conditions are shown in Table 1.
[0059] Comparative Example 1 to Comparative Example 3
[0060] The preparation steps of Comparative Examples 1 to 3 are the same as those of Example 1. The specific general formula of the ternary positive electrode material and the sintering conditions are shown in Table 1.
[0061] Table 1
[0062]
[0063]
[0064] Experimental example
[0065] Battery cell production:
[0066] The ternary positive electrode material was uniformly mixed with conductive carbon black Super P, carbon nanotubes CNT, polyvinylidene fluoride PVDF and N-methylpyrrolidone NMP in a mass ratio of 97.2:1.0:0.8:1.0:100 to obtain a positive electrode slurry, and the slurry was uniformly coated on aluminum foil and dried to obtain a positive electrode sheet. The sheet was rolled to a compaction density of 3.45g / cm 3, and obtain a rolled positive electrode sheet.
[0067] The negative electrode active material, conductive agent, thickener and binder are mixed in a certain mass ratio, and then a solvent is added and stirred thoroughly to obtain a negative electrode slurry. Among them, the negative electrode active material is crystalline carbon. The conductive agent is acetylene black, the thickener is carboxymethyl cellulose sodium (Carboxy methyl Cellulose-Na, CMC-Na), the binder is styrene-butadiene rubber (SBR), and the solvent is deionized water. The obtained negative electrode slurry is evenly coated on the negative electrode collector, which is copper foil, and the negative electrode sheet is obtained after drying, cold pressing and slitting processes. The mixing ratio of the negative electrode active material, conductive agent, thickener and binder is 96.4:1:1.2:1.4.
[0068] Polar solvents are mixed in a certain volume ratio to form an organic solvent system. The polar solvents are selected from ethylene carbonate, ethyl methyl carbonate and diethyl carbonate, and the volume ratio is, for example, 1:1:1. A fully dried lithium salt is then dissolved in the organic solvent system to prepare an electrolyte with a concentration of, for example, 1 mol / L. The lithium salt is selected, for example, lithium hexafluorophosphate (LiPF6). A porous polyethylene membrane is selected as the diaphragm. The thickness of the diaphragm is 11 μm, and the air permeability of the diaphragm is, for example, 200 s / 100 mL, and the porosity is, for example, 40%.
[0069] The rolled positive electrode sheet, graphite negative electrode, separator and electrolyte were combined into a soft-pack battery cell with a capacity of 1Ah, and its electrical performance was measured.
[0070] Electrical performance test:
[0071] The soft-pack battery cell is placed at 25°C, charged to 4.35V using a constant current of 0.33A, and then charged to a cut-off current of 50mA using a constant voltage of 4.35V; then discharged to 2.8V using a constant current of 0.33A. The discharge capacity is recorded as the 25°C capacity, and the discharge energy is recorded as the 25°C energy.
[0072] The soft-pack battery cell was placed at 25°C, charged to 4.35V using a constant current of 0.33A, and then charged to a cut-off current of 50mA using a constant voltage of 4.35V. The soft-pack battery cell was then placed at -20°C for 3 hours to balance it to a stable state, and discharged to 2.5V using a constant current of 0.33A. The discharge capacity is recorded as the -20°C capacity, and the discharge energy is recorded as the -20°C energy.
[0073] High-temperature storage gas production test method: At room temperature, charge to 4.35V at a rate of 0.33C, and use the drainage method to record the initial volume V1 of the battery. Then store the battery in a 60℃ constant temperature oven. Every 7 days, take the battery out of the oven, let it stand at room temperature, test the volume of the battery, and record it as V7. Then charge the battery to 4.35V at a rate of 0.33C, and store the battery in a 60℃ constant temperature oven again. Every 7 days, take the battery out of the oven, let it stand at room temperature, test the volume of the battery, and record it as Vx, where x is the number of days the battery is stored. The test is carried out in this way. The volume change of the battery compared to V1 corresponds to the amount of storage gas produced by the battery cell. The gas production calculation formula of the battery is: (Vx-V1) / V1×100%.
[0074] Table 2
[0075]
[0076]
[0077] Comparative Examples 1 to 3 do not design appropriate second firing conditions, second firing coating agents, and third firing conditions, resulting in a low Od value on the surface of the material and poor low-temperature discharge performance.
[0078] Comparison of Examples 1-3 and the comparative example shows that the type of the sintering coating agent, sintering conditions, and the ratio of the main material elements have an impact on the results of Od and Dmin / D50. When in a better range of interval conditions, the uniformity of the positive electrode material, its low temperature performance, and high temperature gas production performance have advantages.
[0079] Comparison of Examples 7-9 and Comparative Example 2 shows that the three-time coating of the material has a certain influence on the low-temperature performance. When in a better interval condition range, the positive electrode material has a more suitable Od and Dmin / D50 value, and its low-temperature performance and high-temperature gas production performance are both advantageous.
[0080] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a ternary positive electrode material, characterized in that: The following steps are involved: (a) sintering and pulverizing a mixed system containing a lithium source, a ternary precursor and a first doping element; (b) subjecting the mixed system containing the pulverized product and the coating agent to secondary sintering; (c) sintering a mixed system containing the secondary sintered product and the second doping element for a third time to obtain the ternary positive electrode material.
2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The primary sintering temperature is 820-940°C; And / or, the primary sintering time is 10 to 20 hours.
3. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The secondary sintering temperature is 700-900°C; And / or, the secondary sintering time is 6 to 12 hours.
4. The method for preparing a ternary positive electrode material according to claim 1, characterized in that: The temperature of the three sinterings is 400-500°C; And / or, the time of the three sinterings is 1 to 3 hours.
5. The method for preparing the ternary cathode material according to claim 1, characterized in that: The coating agent includes at least one of CoO, CoOOH, Co2O3, Co3O4, NiO or Ni2O3.
6. The method for preparing a ternary cathode material according to claim 1, characterized in that: Includes at least one of the following technical features: (1) The ratio of the molar number of lithium in the lithium source to the total molar number of the first doping element and the second doping element is 0.98-1.05:0.01-0.01; (2) the first doping element includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb or Ta; (3) The second doping element includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb or Ta.
7. The method for preparing a ternary cathode material according to claim 1, characterized in that: The chemical formula of the ternary precursor is Ni a Co b Mn (1-a-b) (OH)2, where 0.55≤a≤0.75, 0.02≤b≤0.15; And / or, the molar ratio of lithium in the lithium source to nickel in the ternary precursor is 0.98-1.05:0.55-0.
75.
8. The ternary positive electrode material prepared by the method for preparing the ternary positive electrode material according to any one of claims 1 to 7.
9. A positive electrode sheet, characterized in that: The invention comprises a ternary positive electrode material prepared by the method for preparing a ternary positive electrode material according to any one of claims 1 to 7 or a ternary positive electrode material according to claim 8.
10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.